(untitled) (Argos, 2025)
This article explains some peculiar phenomena featured in the hexameters of four Latin authors of different ages: Ennius (II b.C.), Silius Italicus and Valerius Flaccus (I b.C.), and Claudian (IV-V a.D.). These studied features offer solutions to the structural problems of dactylic versification.